Aplikasi Pembelajaran Penjaskes Olahraga Basket Menggunakan Metode Computer Assisted Instruction (CAI) - Fricles Ariwisanto Sianturi (Journal Of Informatic Pelita Nusantara, 2016)
Basketball is a big ball game. The game is played by two teams facing each other. Each team is five. The main purpose of this game is to insert the ball as much as possible into the opponent 's basket. The basketball game has a variety of techniques including Basics and Ballast Engineering Techniques Firing Basketball where the technique requires a specific understanding to be easily understood by students. In addition to using live practice learning method of basketball learning still using aids in the form of pictures in the book and described verbally. This makes the students easy to forget about the techniques taught because of time constraints. Learning is the aid given by educators so that the process of acquiring knowledge and knowledge, the mastery of skills and habits and the formation of attitudes and beliefs in the learners. Everything related to learning should be technically good in order to produce a positive output. The Computer assisted Instruction (CAI) learning method is a programmed learning that uses computers as a primary means or aids that communicate material to students, with this method of computer being used to assist learning processes in delivering pre-programmed materials. To achieve effective teaching objectives and students conduct learning activities by interacting with computer systems.Keywords: Basketball, Learning, Computer assisted instruction (CAI).